(untitled) (Sport and Exercise Psychology, 2025)
The present study was motivated by the recognition of a disciplinary gap, namely the tendency within sport psychology to focus almost exclusively either on the negative aspects of affects and emotions or on peak moments conceived as states to be artificially reproduced, often in ways that are not particularly realistic. It was therefore considered important to shift the center of attention toward the positive psycho-cognitive and identity–existential outcomes that high-arousal positive affects and emotions are capable of eliciting within a specific sport activity, namely skyrunning. Indeed, it is widely acknowledged that sport produces beneficial effects in terms of psychophysical well-being; however, a coherent theoretical and conceptual framework that can adequately account for these evident benefits is still lacking. Given the specific sport activity at the core of the present investigation, the focus was further broadened to include environmental variables, which likewise precede and shape the process under consideration. On the basis of an extensive review of the literature, the Broaden-and-Build Theory was identified as the most relevant framework to guide the overall theoretical structure of the study; at the same time, substantial importance was assigned to contributions drawn from environmental psychology. Three reference variables were defined a priori, which, through a cascading sequence of multiple phases, ultimately give rise to two macro-categories of outcomes: one termed the “mind-expansion effect,” and the other the “existential/identity dimension.” Overall, this approach clarified the topic, strengthened the initial hypotheses, and laid the groundwork for a subsequent phase of research.